Random mating and the lack of sex-biased kin clustering in an island population of the bull-headed shrike, Lanius bucephalus. Issue 3 (4th May 2023) - Nomano, Fumiaki Y.; Matsui, Shin; Senda, Mariko; Tsuchiya, Yuko; Takagi, Masaoki
Abstract : The encounter with relatives at the time of mating can be reduced if one or both sexes breed away from the natal site, and it is often assumed that this occurs to a lesser extent on islands where only short dispersal is possible. However, endemic insular populations may have evolved fine-tuned dispersal patterns enabling effective avoidance of inbreeding even in a small habitat, and the influence of spatial constraint should be more apparent for non-endemic than endemic populations. Recently established island populations of originally migratory birds can provide insights into the direct effect of habitat area on inbreeding risk. We studied spatial distribution of kin and inbreeding in a population of the bull-headed shrike, Lanius bucephalus, that became established on small oceanic islands separated from the mainland by > 360 km, Minami-daito and Kita-daito Islands, early in the 1970s. Sex-specific spatial genetic structure that could reduce inbreeding risk was absent within the focal Minami-daito Island. This result remained unchanged after the neighbouring Kita-daito Island was incorporated into the analysis. Average relatedness of breeding pairs was not different from that expected under random mating, and FIS was no greater than zero. The estimates of extra-pair paternity frequency were not high (4.5–16% of offspring, depending on the estimation method) compared to the mainland. Inbreeding coefficient of offspring was variable among nests, indicating some occurrence of inbreeding. We found no clear evidence of recent population bottleneck, suggesting that the purging of deleterious recessive alleles did not occur upon colonisation. These results suggest the absence of obvious inbreeding avoidance despite the potentially negative effects of inbreeding. Future studies should quantify inbreeding depression and also formally rule out the possibility that inbreeding is not avoided as an adaptive strategy as has been suggested for endemic island species. HIGHLIGHTS: Inbreeding risk is assumed to be high in small isolated habitats due to limited dispersal distance. We studied spatial kin clustering and inbreeding in a non-endemic island bird population. Evidence suggests that inbreeding is not avoided via differential dispersal distance between sexes.